Periodontitis and its higher levels of severity are associated with the triglyceride/high density lipoprotein cholesterol ratio. Issue 11 (13th April 2021) - Gomes‐Filho, Isaac S.; Santos, Pedro N. P.; Cruz, Simone S.; Figueiredo, Ana C. M. G.; Trindade, Soraya C.; Ladeia, Ana M.; Cerqueira, Eneida M. M.; Passos‐Soares, Johelle S.; Coelho, Julita M. F.; Hintz, Alexandre M.; Barreto, Maurício L.; Fischer, Ricardo G.; et al.
Abstract: Background: Periodontitis and the Triglyceride/High Density Lipoprotein Cholesterol (TG/HDL‐C) ratio have both been associated with cardiovascular disease, metabolic syndrome, and obesity. Additionally, the ratio is a possible substitute for predicting insulin resistance. This study investigated the association between periodontitis, its severity levels (exposures), and the TG/HDL‐C ratio (outcome). Methods: A cross‐sectional study of public health service users in Brazil considered socioeconomic‐demographic characteristics, lifestyle behavior, and general and oral health conditions. Anthropometric measurements and blood pressure were also measured. Systemic biomarker data were obtained, as well as assessment of periodontal diagnosis and its severity. The TG/HDL‐C ratio was calculated using the serum triglyceride level over HDL cholesterol and the cut‐off point, TG/HDL‐C ≥2.3 serving as the cutoff indicting dyslipidemia. Logistic and linear regressions were used to statistically analyze the data. Results: A total of 1011 participants were included, with 84.17% having periodontitis and 49.85% having a TG/HDL‐C ratio ≥2.3. For individuals with periodontitis, the odds of TG/HDL‐C ratio ≥2.3 were 1.47 times greater than in those without periodontitis (ORAdjusted  = 1.47, 95% CI: 1.02–2.14). Similar results were found for those with moderate and severe periodontitis, with a slight increase in the measurement magnitude with disease severity. Conclusion: A positive relationship between periodontitis and the TG/HDL‐C ratio ≥2.3 was found, suggesting a possible association with periodontal disease severity.